Differential game with many pursuers when controls are subjected to coordinate-wise integral constraints - Alias, Idham Arif; Ibragimov, Gafurjan; Kuchkarov, Atamurat; Sotvoldiyev, Akmal (Institute for Mathematical Research, Universiti Putra Malaysia, 2016)
In this paper, we study a differential game of many pursuers and one evader in R2. The motions of all players are simple. An integral constraint is imposed on each coordinate of the control functions of players. We say that pursuit is completed if the state of a pursuer coincides with that of the evader at some time. The pursuers try to complete the pursuit, and the evader tries to avoid this. Sufficient conditions for completion of the differential game were obtained. The strategies of the pursuers are constructed based on the current values of control parameter of the evader. Also an illustrative example is provided.